Анатолий Русских: биография отдельного лица / [редактор Ю. В. Кузнецов] - Кузнецов Ю. В. (Удмуртия, 2008)
Экземпляры: ЦБ (20080821) / Инвентарный номер: 40215 / Цена: 200.00 / Авт.знак: Р 88 / ББК: 85.143(2Рос=Удм)